Delivery of Therapeutics and Molecules Using Self-Assembled Peptides - Sundar, S.; Chen, Y.; Tong, Y.W. (Current Medicinal Chemistry, 2014)
The use of nanobiotechnology in the formulation of drug carriers has been gaining popularity in recent years. Peptide self-assembly technology is a particularly attractive option due to its simplicity and programmability. Selfassembling peptide amphiphiles are surfactant-like molecules that are capable of spontaneous organization into a variety of nanostructures. The structural and functional features of these nanostructures can be designed through alterations to the peptide sequence. With a keen understanding of the supramolecular principles governing the non-covalent interactions involved, drug loading strategies can be customised. Hydrophobic drugs can be hidden within the core via aromatic interactions while gene-based therapeutics can be complexed with a cationic region of lysine residues. This review article focuses on the application of self-assembling peptide amphiphiles to drug delivery in the area of anti-cancer therapeutics, protein- and peptide-based therapeutics and nucleic acid-based therapeutics. Specific examples are used to discuss the various systems available and emphasis is given to the encapsulation and release mechanism.
Keywords: growth factors